Pengembangan Multimedia Pembelajaran dengan Konteks Arsitektur Rumah Adat Sunda pada materi Kekongruenan dan Kesebangunan - Mukhtarotul Najiba; Hanifah Nurus Sopiany; Septiani Yugni Maudy (STAI Al-Bahjah, 2026)
A preliminary study indicated that students still struggle to grasp the concepts of congruence and similarity because instruction has not sufficiently linked the material to real-life contexts. Limitations regarding visual aids also meant teachers had to spend time manually drawing geometric shapes, while students' knowledge of traditional Sundanese houses remained limited. This study aimed to develop mathematics learning multimedia contextualized around traditional Sundanese house architecture that is valid, practical, and has a potential impact on students' conceptual understanding. The study employed the Research and Development method using the 4D model, comprising the define, design, develop, and disseminate stages. Research instruments included validation sheets for content, media, and language experts; a student response questionnaire; and pre-test and post-test questions. Product assessment involved four teachers and seven lecturers as validators, while trials involved 50 seventh-grade students—10 in the limited trial and 40 in the field trial. The results showed that the multimedia achieved validity scores of 92.50% from content experts, 96.43% from media experts, and 91.67% from language experts. Practicality ratings reached 91.88% in the limited trial and 87.72% in the field trial. The average student score rose from 45.75 on the pre-test to 71.63 on the post-test; thus, the multimedia was deemed highly valid, highly practical, and capable of positively influencing students' understanding of mathematical concepts.